Respostas
respondido por:
1
Se foi definido assim, vamos resolver:
a² + b² = x
a * b = y
(a + b)² = a² + 2ab +b²
(a + b)² = (a² + b²) + 2*(a*b)
(a + b)² = x + 2y
*-*-*-*-*-*-*-*-*-*-*-*-*-*-*
Obrigado pela oportunidade
Boa sorte, bons estudos!
SSRC - 2015
*-*-*-*-*-*-*-*-*-*-*-*-*-*-*
a² + b² = x
a * b = y
(a + b)² = a² + 2ab +b²
(a + b)² = (a² + b²) + 2*(a*b)
(a + b)² = x + 2y
*-*-*-*-*-*-*-*-*-*-*-*-*-*-*
Obrigado pela oportunidade
Boa sorte, bons estudos!
SSRC - 2015
*-*-*-*-*-*-*-*-*-*-*-*-*-*-*
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás